Arabica coffee response to rates of coated and conventional urea in sandy soil - Abranches, Jorge Luiz; Soratto, Rogerio Peres [UNESP]; Perdona, Marcos Jose; Parecido, Renan Jose [UNESP] (Empresa Brasil Pesq Agropec, 2019)
The objective of this work was to evaluate the growth, relative chlorophyll index and nitrogen concentrations in leaves, and the grain yield of arabica coffee (Coffea arabica) fertilized with rates of N as coated and conventional urea, in a sandy soil under rainfed conditions. The experiment was carried out over three crop years, using 'Mundo Novo IAC 388-17-1' coffee, in a randomized complete block design, in a 3x2+1 factorial arrangement, with three treatments with 150, 300, and 600 kg ha(-1) N, as coated and conventional urea, and a control without N, with six replicates. Nitrogen increased stem diameter, plant height, N concentrations and relative chlorophyll index in the leaves, as well as grain yield. Over the three crop years, the highest N rate provided the greatest grain yield. Coated urea has no advantage over the conventional one, in supplying N to arabica coffee crop, in sandy soil under rainfed conditions.
Keywords: Coffea arabica; grain yield; mineral nutrition; nitrogen; slow release